Pattern of Pediatric Poisoning and Accident in Patan Hospital - Chhetri, Uma Devi; Ansari, I; Shrestha, S (Kathmandu University Medical Journal, 2013)
Background Kerosene, drugs, pesticides are chemicals used in home and farms. But because of parents’ or caretakers’ negligence; accidents and poisoning in children may take life of a child. Objective To study the common causes and outcome of pediatric accident and poisoning cases admitted in Patan Hospital. Method A prospective (2068-69) and retrospective (2066-67) studies of pediatric accident and poisoning cases admitted in Patan Hospital (2066-chaitra 2069) were done. Result Out of 44 registered cases total 35 cases were collected in last 4 years. Twenty one in prospective and 14 in retrospective study. Male female ratio was 1.2:1. Most vulnerable age group was 1-5 years (21) and 11-15 yrs (8). Most common poison was pesticide (11), kerosene (9) and drugs (7). Twenty percent were suicidal, 3% were homicidal and rest was accidental. Suicidal poisoning was common in 11-14 years. Accidental poisoning was: taking kerosene from mineral water bottle for water. Small children took drugs and pesticides due its easy availability or careless storing. Five common accidents were near drowning (2), hot water scald, hanging and fall from height. Outcome was 2 expired; 1 Organo-phosphorous and 1 food poisoning. Mortality was 6%. One hanging survived as vegetation. Conclusion Accident and poisoning are preventable. We need to make our home and surrounding poison and accident proof. Small children should never be left unattended. Drugs, pesticides, hot things, and sharp instruments should be kept out of reach of children and in child proof container in separate places. Pesticide should not be sold to children. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 39-43 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8016